Painless math intermediate algebra - Padua, Alicia L. (Anvil, 2008)
"A handy book covering the learning competencies required for Intermediate Algebra. It focuses on the basic concepts and skills development which are explained in simple straightforward language. This book has been especially written for self-study and can be used as a supplementary material for classroom instruction; as a source of appropriate drill exercises; and as a means of convenient and effective review."--Introduction.